What do we know about who does and does not attend general health checks? Findings from a narrative scoping review - Dryden Ruth; Williams Brian; McCowan Colin; Themessl-Huber Markus (BMC, 2012)
Abstract Background General and preventive health checks are a key feature of contemporary policies of anticipatory care. Ensuring high and equitable uptake of such general health checks is essential to ensuring health gain and preventing health inequalities. This literature review explores the socio-demographic, clinical and social cognitive characteristics of those who do and do not engage with general health checks or preventive health checks for cardiovascular disease. Methods An exploratory scoping study approach was employed. Databases searched included the British Nursing Index and Archive, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane Database of Systematic Reviews (CDSR) and Database of Abstracts of Reviews of Effects (DARE), EMBASE, MEDLINE, PsycINFO and the Social Sciences Citation Index (SSCI). Titles and abstracts of 17463 papers were screened; 1171 papers were then independently assessed by two researchers. A review of full text was carried out by two of the authors resulting in 39 being included in the final review. Results Those least likely to attend health checks were men on low incomes, low socio-economic status, unemployed or less well educated. In general, attenders were older than non-attenders. An individual's marital status was found to affect attendance rates with non-attenders more likely to be single. In general, white individuals were more likely to engage with services than individuals from other ethnic backgrounds. Non-attenders had a greater proportion of cardiovascular risk factors than attenders, and smokers were less likely to attend than non-smokers. The relationship between health beliefs and health behaviours appeared complex. Non-attenders were shown to value health less strongly, have low self-efficacy, feel less in control of their health and be less likely to believe in the efficacy of health checks. Conclusion Routine health check-ups appear to be taken up inequitably, with gender, age, socio-demographic status and ethnicity all associated with differential service use. Furthermore, non-attenders appeared to have greater clinical need or risk factors suggesting that differential uptake may lead to sub-optimal health gain and contribute to inequalities via the inverse care law. Appropriate service redesign and interventions to encourage increased uptake among these groups is required.